Pengaruh Viskositas Fluida Terhadap Sifat Hydrophobic dari Berbagai Macam Daun - Dahlia Gusrita (PILLAR OF PHYSICS, 2014)
Most human uses material is a material that is susceptible to liquid. The risk of material quickly and easily damaged when exposed to dirty liquid. Each liquid has a viscosity different, so it needs some information about the characteristics of the material is hydrophobic in nature to be applied in the manufacture of the material. The purpose of this study was to determine the effect of fluid viscosity on the hydrophobic properties of various kinds of leaves. From this research, the contact angle values obtained on average at each leaf with a variation of fluid distilled water, grease and oil . Value of the average contact angle generated at each sample starfruit leaves, cassava leaves and leaf velvetleaf with distilled water fluid (η=0.0538Ns/m2), oil (η=0.1352Ns/m2), and oil (η=0.1835Ns/m2) respectively were 122.3500, 49.7200 and 43.7500 on the leaves starfruit, 127.4400, 49.4200 and 26.1500 in the cassava leaves, 131.9200, 45.5600 and 17.700 in the leaves of velvetleaf . So this study shows that the viscosity of the fluid affect the value of the contact angle and hydrophobic properties, ie the greater the viscosity the smaller the contact angle and hydrophobic properties on the wane . Keywords: Hydrophobic , contact angle , viscosity , Genjer leaves , Carambola Leaves , Leaves Cassava